Association Between Diabetes Mellitus and Secretor (ABH) Status - Alam, MM Ul; Islam, Monwarul; Khan, MMR; Rahman, MK (TAJ: Journal of Teachers Association, 2018)
Five hundred and seventy seven patients with diabetes mellitus showed ABO blood group frequencies closely similar those expected from the controls. Four hundred and eleven patients with diabetes mellitus showed frequencies of secretion and non-secretion of the ABH (O) substances in the saliva closely similar to those expected from the controls. three hundred and two patients with diabetes mellitus gave MN blood groups frequencies very similar to those expected from the controls. TAJ 2012; 25: 38-41